Foundations of another temple or subsidiary shrine inside the temple complex - Temples of India Project Team (Jio Institute, 2024)
Within the larger temple premises, old foundations of another temple or subsidiary shrine (I) are visible. This foundation is situated diagonally at the right corner to the entrance of the Mahakal shrine and suggests the presence of a shallow mandapa, anatarala and a small garbhagriha in plan. Presently, only the base of the temple is surviving, and the rest of the structure has collapsed. It seems that the pillage of broken fragments in the boundary wall also belongs to this temple. Presently, a Shiva Linga is placed on the floor of the foundation.